Energy Metabolism and Aerobic Respiratory Chain of Vitreoscilla sp. C1: Comparison with β-Proteobacteria - Paul T. Nguyen; Yuyao Hu; Anne Caroline Mascarenhas dos Santos; Pingdong Liang; Benjamin C. Stark; Karina Tuz; Oscar Juárez (Microbiology Research)
As the source of the first reported class of non-mammalian hemoglobin, Vitreoscilla sp. C1 is a historically important microorganism that has offered important clues to understanding how bacteria can thrive at low oxygen tension, with potential applications to wastewater and sludge bioengineering. However, the processes that enable this bacterium to thrive in such environments remain unclear. In this study, we analyzed the published Vitreoscilla sp. C1 genome to predict the core metabolic pathways used by this microorganism to support cell growth under hypoxic conditions, compared them with the predicted metabolism of other important β-proteobacteria, and tested Vitreoscilla’s respiratory activity in vitro in the presence of various substrates and inhibitors. Vitreoscilla sp. C1 carries a functional Krebs cycle and the genes for a branched aerobic respiratory chain, minus the genes for complexes III and IV, and our results show that Vitreoscilla sp. C1 sugar metabolism is carried out through a unique pathway that shunts intermediaries from glycolysis, bypassing phosphofructokinase-I, into the non-oxidative section of the pentose phosphate pathway, reducing its oxygen dependency, which appears as an adaptation to the microaerophilic environment that this organism inhabits. Although Vitreoscilla sp. C1 features a simplified respiratory chain, experimental data demonstrate that all predicted branches are functional, with two main dehydrogenases and two terminal oxidases.